Relationship between admission, extracurricular services and academic achievement in secondary schools: a partial least square (PLS) approach - Suleiman, Yusuf; Hanafi, Zahyah; Taslikhan, Muhajir (IISTE, 2016)
This study investigates the nexus between two dimensions of student personnel services (Admission Services, Extracurricular Services) academic achievement in secondary schools with the particular interest to know the significant impact of these services on students’ academic achievement.It is believed that the provision of these services are determinant factors that fast track the development of the students in the school system.The study is quantitative in nature and adopts a correlation survey method.Instruments titled: “Admission and Extracurricular Services Questionnaires” (AESQ) were adapted from relevant studies to measure the services. Questionnaires were distributed to 379 students in one of the secondary schools in Kwara State, Nigeria.This study secondary data to measure the academic achievement of students. Statistical Package for Social Science (SPSS) and Structural Equation Modelling (Smart PLS) were used to analyze the data.The findings revealed a significant relationship between admission services and academic achievement as well as significant relationship between extracurricular services and academic achievement in school. The study concludes that admission and extracurricular services are essential services that are needed for the development of the school students. The presence of these services stimulates students to achieve academic excellence while the reverse could lead to students’ failure.Thus, this study recommended that schools should ensure that admission processes should be thoroughly done for them to select the best students for placement. Also, extracurricular activities should be provided for students to be developed socially, physically and emotionally.Future studies should focus on other aspects of students personnel services like health, accommodation services, and bursary services etc with a view to assess more on the the impact of the services in education system.